Impact of Smoking on Oncologic Outcomes of Upper Tract Urothelial Carcinoma After Radical Nephroureterectomy - Rink, Michael (2012)
BACKGROUND: Ci garette smoking is a common risk factor for developing upper tract urothelial carcinoma (UTUC). OBJECTIVE: To assess the impact of cigarette smoking status, cumulative smoking exposure, and time from cessation on oncologic UTUC outcomes in patients treated with radical nephroureterectomy (RNU). DESIGN, SETTING, AND PARTICIPANTS: A total of 864 patients underwent RNU at five institutions. The median follow-up in this retrospective study was 50 mo. Smoking history included smoking status, quantity of cigarettes per day (CPD), duration in years, and years from smoking cessation. The cumulative smoking exposure was categorized as light-short-term (≤19 CPD and ≤19.9 yr), moderate (all combinations except light-short-term and heavy-long-term), and heavy-long-term (≥ 20CPD and ≥ 20 yr). INTERVENTIONS: RNU with or without lymph node dissection. No patient received neoadjuvant chemotherapy. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Univariable and multivariable logistic regression and competing risk regression analyses assessed the effects of smoking on oncologic outcomes. RESULTS AND LIMITATIONS: A total of 244 patients (28.2%) never smoked; 297 (34.4%) and 323 (37.4%) were former and current smokers, respectively. Among smokers, 87 (10.1%), 331 (38.3%), and 202 (23.4%) were light-short-term, moderate, and heavy-long-term smokers, respectively. Current smoking status, smoking ≥20CPD ≥20 yr, and heavy-long-term smoking were associated with advanced disease (p values ≤0.004), greater likelihood of disease recurrence (p values ≤0.01), and cancer-specific mortality (p values ≤0.05) on multivariable analyses that adjusted for standard features. Patients who quit smoking ≥10 yr prior to RNU did not differ from never smokers regarding advanced tumor stages, disease recurrence, and cancer-specific mortality, but they had better oncologic outcomes then current smokers and those patients who quit smoking <10 yr prior to RNU. The study is limited by its retrospective nature. CONCLUSIONS: Cigarette smoking is significantly associated with advanced disease stages, disease recurrence, and cancer-specific mortality in patients treated with RNU for UTUC. Current smokers and those with a heavy and long-term smoking exposure have the highest risk for poor oncologic outcomes. Smoking cessation >10 yr prior to RNU seems to mitigate some detrimental effects. These results underscore the need for smoking cessation and prevention programs.